EFL Teachers’ Perception Toward The Integration of Technology For ELT in The 2013 Curriculum and Independence Curriculum - Febria, Desty; Teresa, Amelia; Marsevani, Maya (UNIB Press, 2024)
In Indonesia especially 2013 Curriculum and Independence Curriculum, technology play its role for ELT in EFL classroom. Based on the experience of the researcher during her pre-service teaching, teachers in school lack technological devices as well as understanding towards technology of its importance and effectiveness for teaching and learning outcomes, therefore, this study wishes to discuss the importance and effectiveness of technology for EFL teaching. In this study, the researcher uses mixed methods analysis of analyzing quantitative data and qualitative data. 42 Indonesian EFL teachers analyzed divided into 25 teachers in 2013 Curriculum and 17 teachers in Independence Curriculum from all grades (elementary, junior high, and senior high) of either professional or pre-service teaching background, and the research data were collected via an online questionnaire created in Google Forms. In the findings, average of 36% teachers strongly agree and 50% teachers agree from 25 teachers in 2013 Curriculum agree as well as average of 40% teachers strongly agree and 57% teachers agree towards the first issue – importance of technology for ELT in EFL classroom, while the second issue – effectiveness of technology for ELT In EFL classroom resulted average of 50% teachers strongly agree and 40% teachers agree in 2013 Curriculum, and 42% teachers and 54% teachers agree in the Independence Curriculum. The study concludes by highlighting the importance and effectiveness of technology in education, recommending it for Indonesia EFL classroom, particularly in relation to the 2013 Curriculum and Independence Curriculum.